Pengaruh Beban Kerja, Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan pada BUM Desa Amanah Desa Bukit Gajah Pelalawan Provinsi Riau - Sehani; Fajri Prasetyo (Yayasan Almanar Pujud, 2025)
This study aims to determine the effect of workload, work environment, and work motivation on employee performance At BUM Des Amanah, Bukit Gajah Village, Pelalawan, Riau, This research method uses a quantitative approach. The population in this study were employees of Bum Des Amanah Bukit Gajah Village Pelalawan Riau , the samples used was 38 respondents. The data collection method in this study used hypothesis testing and the data analysis used was multiple linear regression through the SPSS 23 program. The results of this study indicate that workload and work motivation have a positive and significant effect on emmployee performance at Bum Des Amanah Bukit Gajah Village Pelalawan Riau, while the work environment has a negative and significant effect on emmployee performance at BUM Des Amanah Bukit Gajah Village Pelalawan Riau. The adjusted R Square value is 0,806 or 80,6% which means employee performance can be explained by workload, work environment, and work motivation, the remaining 19,4% can be influenced by other factors not examined in this study.